A fluidized-bed model for NiMgW-catalyzed CO2 methanation - Jia, Chunmiao (2021)
The reduction of carbon dioxide to methane by hydrogen (“CO2 methanation”) using renewable energy is a promising process for recycling CO2. Better catalysts and better reactors are both required for the practical application of CO2 methanation. This study examines how the operating parameters affect CO2 methanation in a highly efficient fluidized-bed reactor. We first measured the kinetics of the CO2 methanation reaction using an NiMgW catalyst, which has been reported to exhibit superior catalytic performance. We then developed a fluidized-bed reactor model based on an earlier model for CO2 methanation. The fluidized bed model indicated that the NiMgW was indeed superior to two other previously studied catalysts in terms of faster conversion of reactants and higher concentrations of product CH4 throughout the reactor. The overall rate of production of CH4 increased with temperature and H2/CO2 ratio and decreased as the inlet reactant flow rate, catalyst particle diameter, and catalyst particle sphericity increased.